2020
DOI: 10.15388/infedu.2020.22
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Multiple Intelligence Profiles of First-Year IT Students and Employed Graduates

Abstract: The aim of the article is to determine in the studied groups the multiple intelligence distribution defined in the 1980s by Howard Gardner. The research was conducted in three groups of respondents. The first study group was first-year students of computer science, the second was master (2nd degree) students, educationally 4 years older than the first group. Their intelligence distributions were compared with the intelligence distributions of the third group-graduates of the same university, the same field of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Taking these aspects into account, it can be concluded that the thesis put forward by the authors of this paper about the existence of a certain model of intelligence distribu-tion seems justified and indirectly confirmed by the results from many different environments of the world's countries. This thesis appeared earlier in the quoted here work of Wilinski A., Kupracz L. (2020).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Taking these aspects into account, it can be concluded that the thesis put forward by the authors of this paper about the existence of a certain model of intelligence distribu-tion seems justified and indirectly confirmed by the results from many different environments of the world's countries. This thesis appeared earlier in the quoted here work of Wilinski A., Kupracz L. (2020).…”
Section: Discussionmentioning
confidence: 76%
“…We can judge it on the basis of statistical indications mentioned e.g. in the paper by Wilinski and Kupracz (2020). Polar diagrams presented in this paper have regular distributions with approximately equal saturation along each ray representing different sub intelligence (e.g.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation